2016
DOI: 10.1152/jn.00978.2015
|View full text |Cite
|
Sign up to set email alerts
|

Utility of EEG measures of brain function in patients with acute stroke

Abstract: EEG has been used to study acute stroke for decades; however, because of several limitations EEG-based measures rarely inform clinical decision-making in this setting. Recent advances in EEG hardware, recording electrodes, and EEG software could overcome these limitations. The present study examined how well dense-array (256 electrodes) EEG, acquired with a saline-lead net and analyzed with whole brain partial least squares (PLS) modeling, captured extent of acute stroke behavioral deficits and varied in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 46 publications
3
89
1
4
Order By: Relevance
“…Furthermore, restoration of cerebral blood flow following administration of a tissue plasminogen activator was associated with normalization of delta power within minutes (Finnigan et al, 2006). Wu et al (2016) report a positive correlation between ipsilesional delta power and infarct volume which appears to support previous findings indicating a relationship between delta power and cerebral blood flow following ischemic stroke. However, the relationship between beta power and impairment may reflect the importance of beta oscillations to motor function.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, restoration of cerebral blood flow following administration of a tissue plasminogen activator was associated with normalization of delta power within minutes (Finnigan et al, 2006). Wu et al (2016) report a positive correlation between ipsilesional delta power and infarct volume which appears to support previous findings indicating a relationship between delta power and cerebral blood flow following ischemic stroke. However, the relationship between beta power and impairment may reflect the importance of beta oscillations to motor function.…”
supporting
confidence: 81%
“…Recently, Wu et al (2016) investigated the capacity of EEG to capture behavioral impairment shortly following stroke. Resting state EEG recordings were performed in 25 patients between 3 and 12 days post-stroke in complex acute clinical settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, these plastic changes did not translate into functional gains. Nonetheless, research using tMS, fMRI, positron emission tomography (PET), or other novel tools such as high-density array EEG [90, 91] to understand how rehabilitation changes brain function after stroke is of great value in advancing the scientific underpinnings of the field and may aid in designing successful trials.…”
Section: Commentarymentioning
confidence: 99%
“…Advances in digital EEG analysis have overcome limitations of specificity and provided techniques with additional diagnostic value in patients with brain infarcts. For example, interhemispheric spectral asymmetry in the 0.5–25 Hz range estimated with the Brain Symmetry Index predicted that outcome and treatment effect [7, 8], whole brain partial least square models for delta power correlated with the severity of neurological deficit [9], and ipsilateral motor cortex connectivity were associated with effects of physical therapy [10]. In studies with high density arrays, various measures of functional connectivity revealed changes in both ipsi- and contralateral hemisphere that were related to functional recovery [11, 12].…”
Section: Introductionmentioning
confidence: 99%